2013
DOI: 10.1002/rcm.6696
|View full text |Cite
|
Sign up to set email alerts
|

An integrated exact mass spectrometric strategy for comprehensive and rapid characterization of phenolic compounds in licorice

Abstract: The LC/MS analysis for each injection took less than 9 min. The developed method is fast, accurate and reliable due to its high resolution and high efficiency characteristics as a result of combining both UPLC separation and QTOF exact mass measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
63
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 27 publications
6
63
0
Order By: Relevance
“…Many papers have been published proling phenolic compounds in G. glabra samples from different origins and using different extraction methodologies, some of them cited in the previous discussion. 34,35,[37][38][39][40][41][42][43][44][45][46] However, from all of them, only Montoro et al (2011) presented quantitative results, although they cannot be compared with ours results since they are expressed differently (mg g À1 of dry plant), thus these authors revealed liquiritin apioside as the main avonoid present in their sample, which is in agreement with the sample studied herein. In our case, the results were expressed in mg g À1 of extract in order to relate the amounts of phenolic compounds found in the extract to the antioxidant activity.…”
Section: Finally It Was Not Possible To Identify Compound 11 With a supporting
confidence: 83%
“…Many papers have been published proling phenolic compounds in G. glabra samples from different origins and using different extraction methodologies, some of them cited in the previous discussion. 34,35,[37][38][39][40][41][42][43][44][45][46] However, from all of them, only Montoro et al (2011) presented quantitative results, although they cannot be compared with ours results since they are expressed differently (mg g À1 of dry plant), thus these authors revealed liquiritin apioside as the main avonoid present in their sample, which is in agreement with the sample studied herein. In our case, the results were expressed in mg g À1 of extract in order to relate the amounts of phenolic compounds found in the extract to the antioxidant activity.…”
Section: Finally It Was Not Possible To Identify Compound 11 With a supporting
confidence: 83%
“…The negative ion mode was much more suitable for the analysis of this kind of compounds. Except for methyl gallate (21), ethyl gallate (32), protocatechuic aldehyde (18) and succinic acid (4), other 13 phenolic acids including gallic acid (8), protocatechuic acid (13), neochlorogenic acid (16), chlorogenic acid (19), p-hydroxybenzoic acid (20), vanillic acid (24), 2-methoxycinnamic acid (25), caffeic acid (27), 4-hydroxycinnamic acid (35), ferulic Acid (39), 3-hydroxycinnamic acid (45), 2-hydroxycinnamic acid (54) and cinnamic acid (65) had one carboxylic group in their structures, and their characteristic fragmentation behavior was the loss of CO 2 (44 Da) (take cinnamic acid as an example, Fig. 3C).…”
Section: Identification Of Phenolic Acidsmentioning
confidence: 99%
“…These compounds produced two diagnostic fragment [28,29,[35][36][37]. Chalcones with C-2 -OH could transform to corresponding flavanone isomers, and then produced the same typical fragment ions via Y 0 and RDA reaction [28,35]. [35,36].…”
Section: Identification Of Flavonoidsmentioning
confidence: 99%
See 2 more Smart Citations